Produce Basket: The Development of PB module for improving fraction learning - Adams, Deb; Bucci, Terri; McEwan, Lee; Reinthal, Kevin (Ohio Journal of School Mathematics, 2022)
Formal notation of fractions is a critical stumbling block for students, impeding their progress to acquire flexible number sense beyond integers and greatly impacting their success in algebra. Conflicting and vague definitions of fractions are a major cause of confusion and frustration among students and their teachers. Although several authors have identified this lack of clarity and have attempted to help teachers understand fractions better, a successful curriculum unit has not appeared that teachers and students can both use to make the meaning of fractions mathematically precise. To address this lack, a team consisting of a veteran fourth-grade teacher, a professional development leader/university instructor, a math educator, and a mathematician developed an experiential learning module called Produce Basket (PB) for elementary grades fraction learning. The module is a graduated set of games and activities around the metaphor of a basket (standing for "whole") that enables teachers to scaffold the precise definition of a fraction. The aim of this article is to describe the PB learning module with its roots in Bob Moses and the Algebra Project. Additionally, this article will discuss the theory of action that underpins the design of the module.